The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1159/000447441
|View full text |Cite
|
Sign up to set email alerts
|

Telencephalic Neuronal Activation Associated with Spatial Memory in the Terrestrial Toad <b><i>Rhinella arenarum:</i></b> Participation of the Medial Pallium during Navigation by Geometry

Abstract: Amphibians are central to discussions of vertebrate evolution because they represent the transition from aquatic to terrestrial life, a transition with profound consequences for the selective pressures shaping brain evolution. Spatial navigation is one class of behavior that has attracted the interest of comparative neurobiologists because of the relevance of the medial pallium/hippocampus, yet, surprisingly, in this regard amphibians have been sparsely investigated. In the current study, we trained toads to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…Previous studies in amphibians indicated only a secondary role at best for the telencephalon, including the medial pallium, in spatial orientation, it being focused instead on exerting a regulatory influence on the optic tectum [Patton and Grobstein, 1998]. However, in spite of the substantial morphological and connectional differences between the medial pallia of amphibians and amniotes, recent evidence in toads has demonstrated medial pallial participation in navigation by use of external geometric cues [Sotelo et al, 2016;Bingman and Muzio, 2017]. The function of spatial navigation by the hippocampal formation thus appears to be a shared feature across tetrapods.…”
Section: Medial Pallium In Amphibiansmentioning
confidence: 99%
“…Previous studies in amphibians indicated only a secondary role at best for the telencephalon, including the medial pallium, in spatial orientation, it being focused instead on exerting a regulatory influence on the optic tectum [Patton and Grobstein, 1998]. However, in spite of the substantial morphological and connectional differences between the medial pallia of amphibians and amniotes, recent evidence in toads has demonstrated medial pallial participation in navigation by use of external geometric cues [Sotelo et al, 2016;Bingman and Muzio, 2017]. The function of spatial navigation by the hippocampal formation thus appears to be a shared feature across tetrapods.…”
Section: Medial Pallium In Amphibiansmentioning
confidence: 99%
“…The essential role of the hippocampus is particularly noteworthy in tasks that demand encoding of multiple elements and their spatial relationships across different individual episodes in an allocentric internal representation of the space (cognitive map) or requiring a flexible expression of spatial knowledge [O'Keefe and Nadel, 1978;Hartley et al, 2014]. Also, the hippocampal homologue of birds [Sherry and Duff, 1996;Colombo and Broadbent, 2000;Bingman and Sharp, 2006], reptiles [Rodríguez et al, 2002;López et al, 2003;Salas et al, 2003;Holding et al, 2012], and probably amphibians [Sotelo et al, 2016] is consistently involved in map-like spatial memory. From an evolutionary perspective, the similarities in neural mechanisms and functions of the hippocampus across tetrapod taxa could be indicative of a long shared neurobiological ancestry.…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampal involvement in the representation of environmental geometry has been described in a wide variety of vertebrate groups [see Sotelo et al, 2016 for a summary]. Therefore, the medial pallium-boundary geometry coupling found in the terrestrial toad reinforces an inferred ancestral role of the hippocampus in spatial cognition.…”
Section: The Stem Hippocampus: Looking To the Medial Pallium Of Extenmentioning
confidence: 85%
“…In a seminal study, Sotelo et al [2015Sotelo et al [ , 2016 demonstrated in the terrestrial toad, Rhinella arenarum , that locating a goal location using the boundary geometry of a rectangular arena resulted in an upregulation of the immediate-early gene c-fos in the medial pallium. Hippocampal involvement in the representation of environmental geometry has been described in a wide variety of vertebrate groups [see Sotelo et al, 2016 for a summary].…”
Section: The Stem Hippocampus: Looking To the Medial Pallium Of Extenmentioning
confidence: 99%
See 1 more Smart Citation